A Political Economy Analysis of Ghana’s School Feeding Programme - Afrane, O.O (University of Ghana, 2015)
The Ghana School Feeding Programme (GSFP) was introduced as strategic policy to improve the income of beneficiary communities, increase school enrolment and retention and for the achievement of the MDG 2 by the year 2015. In spite of the good intentions of the GSF programme however, it has been bedeviled with a myriad of challenges. Few examples of the challenges identified were; the lack of strict adherence to the carefully written original policy document of the GSFP; the partial payment and delay in payment for the services of caterers; and the banning of the monitoring and evaluation team from doing their work in certain districts due to the powerful role of some political appointees such as the District Chief Executives (DCE‟s) in the implementation of the programme. It was therefore against this background of challenges that the study sought to ascertain how the beneficiaries of GSFP in the Bosomtwe District of Ashanti Region understand the Actors; Institutions and Ideas that pertain to the implementation of the programme and its realization of the MDG 2. A Political Economy Analysis Framework was employed for the study and literature related to political economy and the subject matter was reviewed to reflect on the objectives. A descriptive and explorative survey design was employed in the study. The findings suggested that beneficiaries have little or no idea about the original policy objectives of the GSFP in relation to the actors, institutions and ideas and why certain key political appointees are selected to manage the programme. However, it was also revealed in the findings that the achievement of the universal primary education by the end of 2015 will be difficult to achieve if not impossible. It is strongly recommended that policy makers should include beneficiary communities in the part of the consultation processes in the uptake of a social intervention programme. The study also recommend that the programme is sustain in order to ensure that children are kept in school especially girl child.
Thesis (MA) - University of Ghana, 2015
Keywords: Analysis; School Feeding Programme; Ghana; Economy